Capaian Pelayanan Kesehatan Dasar Di Kota Pekanbaru - Trio Saputra (JURNAL ILMU SOSIAL, 2017)
Minimum service standards hereinafter abbreviated SPM is a provision of the type and quality of basic services that are obligatory area obtained every citizen is entitled to a minimum. Minimum Service Standards health sector Health hereinafter referred SPM is a benchmark performance of health services, held the Regency / City. Health decentralization in Indonesia has been implemented since 2001. Basic health services Pekanbaru City can not be said to be good. Total availability of medical personnel and doctors are not proportional to the population. Distribution of medical personnel and doctors uneven per-districts in the city of Pekanbaru. Besides the availability of health centers, polyclinics and sub Per-districts are also uneven. Pekanbaru city has not had a referral hospital, although their Arifin Achmad.